Preparation Method of Chitosan Oligosaccharide and Chitin Oligosaccharide and Their Application in Aquaculture - Chunlan LU; Bei WANG (Guangdong nongye kexue)
People expect pollution-free and residue-free green aquatic products earnestly. However, in recent years, with the rapid expansion of aquaculture farming density and scale, aquatic animal diseases are frequent, and problems such as strain resistance caused by the abuse of antibiotics have gradually emerged, which bring challenges to the sustainable and green development of aquaculture. Chitosan oligosaccharides and chitin oligosaccharides due to non-toxic, nonharmful, and residue-free characteristics, with a variety of bioactive functions and a wide range of sources, is gradually valued and studied by many scholars. Chitosan oligosaccharides are oligosaccharides obtained from chitin or chitosan by enzymatic, chemical or physical methods. Chitin oligosaccharides are degradation products of chitin or acetylation products of oligochitosan. At present, experimental studies on chitosan oligosaccharides and chitin oligosaccharides as green feed additives, vaccine adjuvants and aquatic products water retention and freshness have been carried out, and they have broad development space and application prospects in aquaculture. Based on this, this review summarizes the preparation methods of chitosan oligosaccharides and chitin oligosaccharides, and discusses the application of Chitosan oligosaccharides and chitin oligosaccharides in aquatic animal feed additives, vaccine adjuvants and aquatic products water preservation and freshness, highlighting their biological activities in regulating aquatic animal immunity, promoting growth, anti-oxidation and affecting fish body composition, with a view to providing references for further research and industrial application of Chitosan oligosaccharides and chitin oligosaccharides in aquaculture.